2013
DOI: 10.4021/jocmr1492w
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Directed Heart Failure Transitional Care Program: A Retrospective Case Review

Abstract: BackgroundDespite a variety of national efforts to improve transitions of care for patients at risk for rehospitalization, 30-day rehospitalization rates for patients with heart failure have remained largely unchanged.MethodsThis is a retrospective review of 73 patients enrolled in our hospital-based, physican-directed Heart Failure Transitional Care Program (HFTCP). This study evaluated the 30- and 90- day readmission rates before and after enrollment in the program. The Transitionalist’s services focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The favorable results of our program were consistent with a home based palliative care program [ 17 ] and shared similarities in patient characteristics such as home bound status, dependency in functional status and high nursing care needs; and interventions that are multi-disciplinary in nature and accessibility to a nurse by phone. A home-based intervention program for heart failure patients consisting of a single home visit within one week of discharge by a nurse and pharmacist to optimize medication management and identify early clinical deterioration [ 18 ] and a physician-directed transitional care program that provided early review at home or clinic setting within 72 hours of discharge, dietary education and follow-up phone reviews reported reductions in unplanned readmissions [ 19 ]. Similar to our program, these two programs targeted patients with high disease burden and baseline readmission risk; and emphasized on early review, medication reconciliation and patient education in the post-discharge period.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable results of our program were consistent with a home based palliative care program [ 17 ] and shared similarities in patient characteristics such as home bound status, dependency in functional status and high nursing care needs; and interventions that are multi-disciplinary in nature and accessibility to a nurse by phone. A home-based intervention program for heart failure patients consisting of a single home visit within one week of discharge by a nurse and pharmacist to optimize medication management and identify early clinical deterioration [ 18 ] and a physician-directed transitional care program that provided early review at home or clinic setting within 72 hours of discharge, dietary education and follow-up phone reviews reported reductions in unplanned readmissions [ 19 ]. Similar to our program, these two programs targeted patients with high disease burden and baseline readmission risk; and emphasized on early review, medication reconciliation and patient education in the post-discharge period.…”
Section: Discussionmentioning
confidence: 99%
“…Tuso et al [ 25 ] also found that providing a transitional care bundle including a timely primary care physician follow-up outpatient visit significantly reduced hospital readmissions in the state of California. Some studies show similar results among patients with different diseases [ 26 , 27 ]. In contrast, other studies show that simply scheduling post-discharge clinic visits does not prevent hospital readmissions in different patient populations [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 87%
“…Various studies have implicated different strategies to bring reduction to the 30-day all-cause readmission rates [ 45 , 46 , 47 , 48 , 51 , 56 , 57 , 58 , 59 , 60 ]. These strategies include: Multidisciplinary HF clinics/centers (reduces all-cause readmission rates by 50%) Visiting nurse services and nurse specialist (reduces all-cause readmission rates by 37%) Physician-directed heart failure transitional care program (reduces all-cause readmission rates by 21%) Home tele-monitoring or structured phone calls (reduces all-cause readmission rates by 20%) Follow-up one-week post discharge (reduces all-cause readmission rates by 10%–15%) Transition care intervention home program (reduces all-cause readmission rates by 6%–12%) These strategies have been further refined through the incorporation of the findings from the completed and ongoing clinical trials (e.g., PCDM- p atient- c entered d isease m anagement, REACH-HF- r ehabilitation e n a blement in ch ronic h eart f ailure [ 61 , 62 ] and Table 2 ).…”
Section: Readmissionmentioning
confidence: 99%
“…Transition home program: This helps patients to have a safe transition to home or to another healthcare setting, such as a skilled nursing facility, and includes thorough patient and caregiver education, enhanced individualized assessment of post-discharge needs, patient-centered communication with caregivers and a standardized process for further management of HF along with follow-up visits with healthcare professionals [ 59 , 60 , 68 ].…”
Section: Quality Improvement Strategies For Hfmentioning
confidence: 99%
See 1 more Smart Citation